Phase Sensitive Parametric Process in Silicon Nano-Waveguides at C-Band Wavelengths - Mahmoud Jazayerifar; Kambiz Jamshidi (IEEE Photonics Journal, 2016)
Using numerical and analytical tools, we compare different phase sensitive parametric schemes namely one pump and two pump schemes for silicon nano-waveguides. The conditions required to achieve phase sensitive gain are obtained, and it is shown that a real continuous wave phase sensitive parametric gain could be possible in the presence of two photon absorption.